THE EU RESEARCH AND INNOVATION POLICY AND INTEGRATION OF THE REPUBLIC OF SERBIA INTO THE REFORMED ERA - Stevanovic, Olga (Serbian political thought, 2023)
This paper addresses the subject of the EU research and innovation policy in the context of the European Research Area reform, with special focus on its external aspect. The first goal of this paper is to describe the leading developments in research and innovation which have taken place in the last decade, with emphasis on their significance for the EU integration process. Starting from Leuffen et al’s concept of external differentiation, in this paper the ERA is considered a policy regime which expands beyond the EU borders. Consequently, the second goal of the paper is to present the Serbian research and innovation policy with respect to the ERA integration after the chapter on science and research was provisionally closed. Through thematic analysis of research and innovation strategies, this paper will discern if Serbian R&I policy converges with the priorities and guidelines of the new ERA, thus rendering it a part of the broader European research landscape.